Review of Non-destructive Testing (NDT) Techniques and their applicability to thick walled composites - Jolly, Mark R.; Prabhakar, Arun; Sturzu, Bogdan; Hollstein, K.; Singh, R.; Thomas, S.; Foote, Peter; Shaw, Andy (Elsevier, 2015)
A tier 1 automotive supplier has developed a novel and unique kinetic energy recovery storage system for both retro-fitting and OEM application for public transport systems where periodic stop start behaviour is paramount. A major component of the system is a composite flywheel spinning at up to 36,000 rpm (600 Hz). Material soundness is an essential requirement of the flywheel to ensure failure does not occur. The component is particularly thick for a composite being up to 30 mm cross section in some places. The geometry, scale and material make-up pose some challenges for conventional NDT systems. Damage can arise in composite materials during material processing, fabrication of the component or in-service activities among which delamination, cracks and porosity are the most common defects. A number of non-destructive testing (NDT) techniques are effective in testing components for defects without damaging the component. NDT techniques like Ultrasonic Testing, X-Ray, Radiography, Thermography, Eddy current and Acoustic Emission are current techniques for various testing applications. Each of these techniques uses different principles to look into the material for defects. However, the geometry, physical and material properties of the component being tested are important factors in the applicability of a technique. This paper reviews these NDT techniques and compares them in terms of characteristics and applicability to composite parts.
Keywords: Carbon composites; thick walled; Non-destructive testing; CFRP; Flywheel; Ultrasonic testing; Thermography; Computed tomography